PENGARUH PERTUMBUHAN EKONOMI, INVESTASI, INFLASI, NILAI TUKAR RUPIAH DAN JUMLAH PENGUSAHA KENA PAJAK TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI (Studi Kasus Penerimaan PPN Di Kanwil DJP Jateng I) - Eko Prasojo, 11.05.52.0197; Wahjudi, Djoko (Students Journal of Accounting and Banking, 2015)
The study examines the effect of economic growth, inflation, investation, exchange rate, and the amount of taxable entrepreneurs towards Value Added Tax (VAT) revenue. This research was conducted at the General Council Tax I of Central Java by analyzing VAT revenue in tax office registered and included in the working area of Central Javaâs General Council Tax I. The sampling method used census method, which means all made in the sample covering tax office registered and included in the working area of Central Javaâs General Council Tax I during 2010 until 2013. Relationship (or) influence between variable is described by using multiple regression analysis. The result showed that the economic growth and the amount of taxable entrepreneurs have positive effect significant to VAT revenue. Whereas investation has nrgatif significant effect to VAT revenue, while inflation and exchange rate have no significant effect to VAT revenue.Keywords: Economi Growth, Investation, Inflation, Exchange Rate, The Amount of Taxable Entrepreneurs, and Value Added Tax (VAT) Revenue